2022
DOI: 10.7554/elife.78945
|View full text |Cite
|
Sign up to set email alerts
|

A neurogenic signature involving monoamine Oxidase-A controls human thermogenic adipose tissue development

Abstract: Mechanisms that control 'beige/brite' thermogenic adipose tissue development may be harnessed to improve human metabolic health. To define these mechanisms, we developed a species-hybrid model in which human mesenchymal progenitor cells were used to develop white or thermogenic/beige adipose tissue in mice. The hybrid adipose tissue developed distinctive features of human adipose tissue, such as larger adipocyte size, despite its neurovascular architecture being entirely of murine origin. Thermogenic adipose t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 70 publications
0
5
0
Order By: Relevance
“…6a ) and generate a functional human/mouse hybrid adipose depot (Fig. 6b ) 33 . Analysis of human transcript-specific reads in adipose tissue formed 8 weeks after implantation revealed expected expression of human adipocyte genes, as well as expression of mesenchymal progenitor markers and canonical Wnt target genes (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…6a ) and generate a functional human/mouse hybrid adipose depot (Fig. 6b ) 33 . Analysis of human transcript-specific reads in adipose tissue formed 8 weeks after implantation revealed expected expression of human adipocyte genes, as well as expression of mesenchymal progenitor markers and canonical Wnt target genes (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Methods for the collection and culture of adipose tissue explants were previously published 33 . In brief, ~10 7 passage 3 human adipose tissue derived progenitor cells were thawed into 150-mm plate and after 72 h they were split 1:2 at a dense seeding density of ~8 × 10 6 cells per 150-mm plate.…”
Section: Methodsmentioning
confidence: 99%
“…An et al [31] discovered that regardless of genetic and other clinical factors, methylation variation in the MAOA gene promoter is related to fasting plasma glucose. Solivan-Rivera et al [32] identifed mechanisms that regulate the formation of thermogenic adipose tissue and suggested that human adipocyte MAOA could serve as a potential therapeutic target for metabolic disorders. Our molecular docking analysis of eugenol and MAOA refected that the hypoglycemic mechanism may be bound up with inhibiting MAOA by eugenol after a high-fat diet.…”
Section: Discussionmentioning
confidence: 99%
“…It is well established that humans are born with classical brown adipose tissue localized to the interscapular and perirenal regions 49 with the interscapular depot regressing in the first and second decade of life 17,20 and the perirenal depot slowly transforming into a white adipose tissue depot 50 . Since thermogenic adipose tissue increases insulin sensitivity and energy expenditure to suppress the development of diabetes and obesity, there are currently numerous efforts to find therapeutic approaches to induce the formation of beige adipose tissue [51][52][53] . However, an alternative approach would be to prevent the regression of brown adipocytes that are present at birth.…”
Section: Discussionmentioning
confidence: 99%